👤

Simplify the algebraic expression:
50xy - 55xy² + 63xy + 70xy²


Sagot :

Answer:

1.

= 2x + 3y + 5x + 6y \\  = 2x + 5x + 6y + 3y \\  = 7x + 9y

2.

= 7 - 3a + 5a + 15 \\  =  - 3a + 5a + 15 + 7 \\  = 2a + 22

3.

= fg - 5fg - g + 3f \\  =  - 4fg  + 3f - g

4.

= 6 {lm}^{2}  -  {5l}^{2} m -  {17lm}^{2}  +  {21l}^{2} m \\  = 6 {lm}^{2} -  {17lm}^{2}   - 5 {l}^{2} m +  {21l}^{2} m \\  =  - 11 {lm}^{2}  + 16 {l}^{2} m

5.

= 50xy - 55x {y}^{2}  + 63xy +  {70xy}^{2}  \\  =  - 55 {xy}^{2}  +  {70xy}^{2}  + 50xy + 63xy \\   = 15 {xy}^{2}  + 113xy